2004
DOI: 10.1080/13577140410001679220
|View full text |Cite
|
Sign up to set email alerts
|

Low Dose Histone Deacetylase Inhibitor, Depsipeptide (FR901228), Promotes Adenoviral Transduction in Human Rhabdomyosarcoma Cell Lines

Abstract: Purpose. Transduction of rhabdomyosarcoma (RMS) cells with adenoviral vectors for in vivo and in vitro applications has been limited by the low to absent levels of coxackie and adenovirus receptor (CAR). This study investigates the potential use of low doses of a histone deacetylase inhibitor, depsipeptide (FR901228), currently in Phase II human trials, to enhance adenoviral uptake in six rhabdomyosarcoma cell lines. Methods. Differences in adenoviral uptake in the presence and absence of depsipeptide (FR90122… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…28 There are limited preclinical data reporting the activity of HDAC inhibitors in sarcoma. [31][32][33][34][35][36][37][38][39] Ecke and co-workers observed that combined 5-aza-2′deoxycytidine (a DNA methylation inhibitor) and valproic acid (a HDAC inhibitor) efficiently prevented medulloblastoma and rhabdomyosarcoma formation in patched mutant mice. 32 Nguyen and co-workers observed that the Hsp90 inhibitor 17-AAG and the HDAC inhibitor MS-275 had synergistic, antiproliferative, and proapoptotic effects on synovial sarcoma in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…28 There are limited preclinical data reporting the activity of HDAC inhibitors in sarcoma. [31][32][33][34][35][36][37][38][39] Ecke and co-workers observed that combined 5-aza-2′deoxycytidine (a DNA methylation inhibitor) and valproic acid (a HDAC inhibitor) efficiently prevented medulloblastoma and rhabdomyosarcoma formation in patched mutant mice. 32 Nguyen and co-workers observed that the Hsp90 inhibitor 17-AAG and the HDAC inhibitor MS-275 had synergistic, antiproliferative, and proapoptotic effects on synovial sarcoma in vitro.…”
Section: Discussionmentioning
confidence: 99%